'On the Road Again': A 118 country panel analysis of gasoline and diesel demand. (December 2020) - Liddle, Brantley; Huntington, Hillard
Highlights: Gasoline price elasticity for OECD is −0.7 (three times that for non-OECD). Diesel price elasticity for OECD is −0.35 (modestly larger than that for non-OECD). Gasoline GDP elasticity for non-OECD is around 1.0 (twice that for OECD). For OECD, diesel GDP elasticity is considerably larger than that for gasoline. For non-OECD, diesel GDP elasticity is similar to that for gasoline. Abstract: The current paper contributes to the literature on the relationship between economic growth, fuel prices, and the demand for gasoline and diesel within the transportation sector by assembling a wide panel dataset of fuel consumption and prices for 35 OECD and 83 Non-OECD countries. The unbalanced data spans 1978–2016, with the full 39 years of data for 36 countries. In addition, our dynamic panel estimates address nonstationarity, heterogeneity, and cross-sectional dependence. The OECD panel price elasticity for gasoline is around −0.7 or about three times that for the non-OECD panel; whereas, the OECD price elasticity for diesel is only modestly larger (in absolute terms) than the non-OECD elasticity (−0.3 and −0.2, respectively). For gasoline, the non-OECD GDP elasticity is around 1.0 or about twice that for OECD countries. For the OECD panel, the diesel GDP elasticity is about three times that of the OECD GDP elasticity for gasoline; whereas, for the non-OECD panel, the two GDP elasticities (for gasoline and diesel) are about the same. For non-OECD countries, subpanels based on geography and income produced mostly similar results. We found no evidence of GDP or price asymmetric effects for the 1978–2016 period. Lastly, the large (at least for the OECD panel) and statistically significant transportation price elasticities reported here provide stark contrast to the economy-wide energy price elasticities calculated in Liddle and Huntington (2020a).